2022
DOI: 10.3389/fnagi.2022.788571
|View full text |Cite
|
Sign up to set email alerts
|

A Spatiotemporal Brain Network Analysis of Alzheimer’s Disease Based on Persistent Homology

Abstract: Current brain network studies based on persistent homology mainly focus on the spatial evolution over multiple spatial scales, and there is little research on the evolution of a spatiotemporal brain network of Alzheimer’s disease (AD). This paper proposed a persistent homology-based method by combining multiple temporal windows and spatial scales to study the spatiotemporal evolution of brain functional networks. Specifically, a time-sliding window method was performed to establish a spatiotemporal network, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Although the pathological mechanisms underlying the neuropathological changes in AD remain unclear, some neuropathological hallmarks have been reported, such as neuritic extracellular amyloid plaques and intracellular neurofibrillary tangles, which would lead to energy slowing down, decrease of complexity and synchrony, and disconnection of the connectivity (Dauwels et al, 2010a ). By complex networks theory and graph theory, recent research on brain functional networks extracted from fMRI ( Table 7 ) and the structural networks extracted from MRI have shown that AD patients have different degrees of local or even global topology abnormalities and “disconnection” symptoms (Xu et al, 2008 ; Sanz-Arigita et al, 2010 ; Córdova-Palomera et al, 2017 ; Khatri and Kwon, 2022 ; Xing et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathological mechanisms underlying the neuropathological changes in AD remain unclear, some neuropathological hallmarks have been reported, such as neuritic extracellular amyloid plaques and intracellular neurofibrillary tangles, which would lead to energy slowing down, decrease of complexity and synchrony, and disconnection of the connectivity (Dauwels et al, 2010a ). By complex networks theory and graph theory, recent research on brain functional networks extracted from fMRI ( Table 7 ) and the structural networks extracted from MRI have shown that AD patients have different degrees of local or even global topology abnormalities and “disconnection” symptoms (Xu et al, 2008 ; Sanz-Arigita et al, 2010 ; Córdova-Palomera et al, 2017 ; Khatri and Kwon, 2022 ; Xing et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have illustrated the versatility of persistent homology in analyzing complex networks, including brain networks. [ 10 , 12 ] highlighted the application of persistent homology in evaluating temporal changes in topological network features. [ 13 ] used persistent homology to detect and track the evolution of networks’ clique.…”
Section: Introductionmentioning
confidence: 99%
“…In C. Liu et al (2021) , persistent homology has been applied to characterize the neuropsychological properties of the brain. In Xing, Jia, Wu, and Kuang (2022) , persistent homology has been used to study the evolution of a spatiotemporal brain network of AD. They have also proposed that persistent homology can be considered as a framework to assess the neurophysiological properties of image quality.…”
Section: Introductionmentioning
confidence: 99%